Population Structure, Site Fidelity, and Residency Patterns of Whale Sharks (Rhincodon typus) in Botubarani Waters, Gorontalo Province, Indonesia - Rahman, Rahman; Suyasa, I Nyoman; Syamsuddin, Awaludin; Pahlevi, Reza Shah (Bogor Agricultural University, Indonesia, 2025)
Whale shark (Rhincodon typus) is the largest fish species in the world and is classified as endangered. This study is crucial for the conservation of this species and developing effective conservation strategies. The research was conducted in the Botubarani waters, Gorontalo Province. Individual whale shark identification was performed using Photo ID, including the identification of sex and wound location. Photo IDs were processed using the Interactive Individual Identification System (I3S) software and includes information related to the ID, body length, and the time the individual was previously identified. Monitoring of the location, number, timing of whale shark presences and water parameters, was carried out through direct field observations. The results showed that 5 whale shark individuals were identified, all of which were male, with lengths ranging from 4.5 to 4.8 meters, and 1 individual had visible wounds. From 78 days of monitoring, Whale sharks were observed for 70 days and not observed for 8 days. The frequency of whale shark appearances ranged from 1 to 4 individuals per day. Whale sharks in Botubarani waters exhibited site fidelity and a mixed migration pattern. The intensity of their presence is quite high. This intensity is supported by ecological conditions that are optimal for the life of whale sharks, particularly those of juvenile age. The measured water parameters significantly influence their presence.